Mapping English language proficiency test scores of lecturers onto the common European framework level - Pane, Isli Iriani Indiah; Putra, Kurnia Hendra; Sembiring, Puan Suri Mira Annisa (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
This study was conducted to display the lecturer’s English language proficiency test scores at one of the state universities in Indonesia. The research applied descriptive design by quantitative approach. The sample is the lecturers of the English and non-English departments at one of the state universities in Indonesia. The instrument of the research was English language proficiency test of TOEFL ITP. Descriptive statistics was used as data analysis technique, mean and percentage. The result of this research disclosed that 86% of the lecturers are in the level of B1 of CEFR which achieved the targeted score of English competences certification file requirements of certified lecturer and 3.92% of the lecturers are in the A2 level of CEFR. The researchers discovered that the most difficult language skill of the test is in the structure and written expression section where 4 % of the lecturers are in the A2 CEFR level. Then it is also revealed that the lecturers got the lowest scaled score in the structure and written expression section, which was 37. From all parts of the test, none of the lecturers achieved C1 level in the structure and written expression. This is implied that the lecturers have problems in their writing skills and need to improve their grammatical skills to be able to write correct sentence structure in standard academic English.